A new species and two new records of Amanita (Amanitaceae; Basidiomycota) from South Korea - Jo, Jong Won; Kwag, Young-Nam; Kim, Hyung So; Lee, Hyun; Han, Sang-Kuk; Han, Jae-Gu; Oh, Seung Hwan; Kim, Chang Sun (Phytotaxa, 2020)
A new species of Amanita sect. Roanokenses, A. brunneofolia, from South Korea, is described based on morphological and molecular evidences. The species is characterized by medium- to large-sized basidiomata, a greenish white pileus covered with brownish, floccose pyramidal volval remnants, an appendiculate margin, reddish brown lamellae, a long radicating stipe, and ellipsoid to elongate amyloid basidiospores. Based on both nrLSU and combined dataset (nrLSU, rpb2 and tef1-α), A. brunneofolia formed a monophyletic clade and clearly separated from other Amanita species. In addition, we describe two other Amanita species in A. sect. Roanokenses, namely, A. caojizong and A. sphaerobulbosa. This is the first report of these species for South Korea.